Otto Tomek: der Rundfunk und die Neue Musik - Jahn, Hans-Peter (Hofheim Wolke, 2018)
The flourishing period of New Music after the Second World War was also the heyday of German radio stations. The music publicist, radio editor, music department head and publishing manager Otto Tomek (1928-2013) was one of the most important personalities of this era. As the first editor for new music, he was responsible for "Musik der Zeit" at WDR, as head of the music department at SWF for the Donaueschingen Music Days and the experimental studio of the Heinrich Strobel Foundation and as head of music at SDR for the Schwetzingen Festival and the Stuttgart Radio Symphony Orchestra.Hans-Peter Jahn paints a portrait of Otto Tomek as a patron, friend and advisor to countless renowned composers such as Karlheinz Stockhausen, Luigi Nono, Pierre Boulez, Bernd Alois Zimmermann, Mauricio Kagel, György Ligeti and Wolfgang Rihm on the basis of many previously unpublished documents and correspondence. Using the example of Otto Tomek's work at WDR, SWF and SDR, the book provides deep insights into the specific characteristics and internal structures of the three broadcasting organisations, into the power and powerlessness of a broadcaster like Otto Tomek.New perspectives on recent music history from the post-war period to the nineties of the last century emerge and it becomes clear what an exclusive and formative role the broadcasting organisations played with their paradisiacal powers of attraction and repulsion, with their promotional activities, but also with their specific evaluation and elimination criteria.(Translated with DeepL.com)
Includes bibliographical references (pages 391-392) and index.
Keywords: Tomek, Otto; 20th Century (1901-2000); 21st Century (2001-2100); Music history; Music criticism; Biography; Germany